IMPLEMENTATION OF INNOVATIVE EDUCATIONAL SYSTEM THROUGH ENGAGING YOUTH TO MASSIVE OPEN ON-LINE COURSES - Larisa Savyuk; Oleksiy Voychenko (Kherson State University, 2016)
Analysis of demographics and migrations on the example of Prykarpattia region demonstrates a worsening of the active and talented youth migration abroad problem. The solution may be to attract young people to receive a free education on the basis of domestic and foreign massive open online courses with a professional focus on the needs of the regіonal labor market. The main obstacle is the poor awareness of modern Ukrainian youth about opportunities for such educational services. At the moment, counseling youth on massive open online courses is practically non-existent. In this paper we propose an approach, that should help to solve this problem. The proposed approach is based on the establishment of a regional data bank of domestic and foreign massive open online courses structured by a professional orientation. The focus is on the needs of young people in rural and mountain regions. Tutoring support from the social organization to choose the directions and learning strategies may increase the motivation of young people to obtain professional competencies and finding opportunities for the rational use of their human capital on the regional labor market